Three new O-isocrotonyl-3-hydroxybutyric acid congeners produced by a sea anemone-derived marine bacterium of the genus Vibrio - Li, Dandan; Harunari, Enjuro; Zhou, Tao; Oku, Naoya; Igarashi, Yasuhiro (Beilstein Journal of Organic Chemistry, 2020)
Liquid cultures of Vibrio sp. SI9, isolated from the outer tissue of the sea anemone Radianthus crispus, was found to produce three new O-isocrotonyl-3-hydroxybutyric acid derivatives, O-isocrotonyl-3-hydroxypentanoic acid (1), O-isocrotonyl-3-hydroxyhexanoic acid (2), and O-(Z)-2-hexenoyl-3-hydroxybutyric acid (3), together with the known O-isocrotonyl-3-hydroxybutyric acid (4). The structures of 1–3 were established by NMR spectroscopy and mass spectrometry, coupled with anisotropy-based chiral analysis, revealing the same R-configuration for all congeners 1–4. The compounds 1–4 were weakly growth-inhibitory against a marine fish ulcer pathogenic bacterium, Tenacibaculum maritimum NBRC16015. Structural similarities among 1–4, the O-isocrotonylated 3-hydroxybutyrate oligomers 5, and microbial biopolymer polyhydroxyalkanoates (PHA) suggest the presence of a common biosynthetic machinery, and hence a possible dehydrative modification at the hydroxy terminus of PHA.
Keywords: 3-hydroxybutyric acid; polyhydroxyalkanoate; sea anemone; Tenacibaculum maritimum; Vibrio

Bergey’s Manual of Systematics of Archaea and Bacteria - Farmer, J. J., III; Janda, J. M.; Brenner, F. W.; Cameron, D. N.; Birkhead, K. M. (Vibrio, 2015)

(untitled) - Parte, A. C. (Int. J. Syst. Evol. Microbiol., 2018)

(untitled) - Mohamad, N.; Amal, M. N. A.; Yasin, I. S. M.; Zamri Saad, M.; Nasruddin, N. S.; Al-saari, N.; Mino, S.; Sawabe, T. (Aquaculture, 2019)

Food Microbiology: Fundamentals and Frontiers - Ceccarelli, D.; Amaro, C.; Romalde, J. L.; Suffredini, E.; Vezzulli, L. (Vibrio Species, 2019)

(untitled) - Kang, S. R.; Srinivasan, S.; Lee, S.-S. (Int. J. Syst. Evol. Microbiol., 2015)

(untitled) - Gómez-Consarnau, L.; Akram, N.; Lindell, K.; Pedersen, A.; Neutze, R.; Milton, D. L.; González, J. M.; Pinhassi, J. (PLoS Biol., 2010)

(untitled) - Gutierrez, C. K.; Matsui, G. Y.; Lincoln, D. E.; Lovell, C. R. (Appl. Environ. Microbiol., 2009)

Dictionary of Natural Products 28.2 Chemical Search

JP Patent - Kikuchi, K.; Chen, C.; Takadera, T.; Nishijima, M.; Araki, M.; Adachi, K.; Sano, H. (New 3-hydroxybutyric acid oligomers and their preparation, 1998)

(untitled) - Nagai, Y.; Kusumi, T. (Tetrahedron Lett., 1995)

(untitled) - Yabuuchi, T.; Kusumi, T. (J. Org. Chem., 2000)

(untitled) - Rehm, B. H. A. (Biochem. J., 2003)

(untitled) - Kaunzinger, A.; Podebrad, F.; Liske, R.; Maas, B.; Dietrich, A.; Mosandl, A. (J. High Resolut. Chromatogr., 1995)

(untitled) - Choi, S. Y.; Rhie, M. N.; Kim, H. T.; Joo, J. C.; Cho, I. J.; Son, J.; Jo, S. Y.; Sohn, Y. J.; Baritugo, K.-A.; Pyo, J.; Lee, Y.; Lee, S. Y.; et al. (Metab. Eng., 2020)

(untitled) - Tullo, A. H. (Chem. Eng. News, 2019)

(untitled) - Baumann, P.; Baumann, L.; Mandel, M. (J. Bacteriol., 1971)

(untitled) - Kavitha, G.; Rengasamy, R.; Inbakandan, D. (Int. J. Biol. Macromol., 2018)

Health Consequences of Microbial Interactions with Hydrocarbons, Oils, and Lipids - Laranja, J. L. Q.; Bossier, P. (Poly-beta-hydroxybutyrate (PHB) and infection reduction in farmed aquatic animals, 2019)

(untitled) - Sharma, A. R.; Zhou, T.; Harunari, E.; Oku, N.; Trianto, A.; Igarashi, Y. (J. Antibiot., 2019)

(untitled) - Oku, N.; Matsumoto, M.; Yonejima, K.; Tansei, K.; Igarashi, Y. (Beilstein J. Org. Chem., 2014)